The Effectiveness of Citrus Limon Extract as A Substitute for Glacial Acetic Acid Solution in The Turks Solution - Merizka, Engla; Harun, Hamdan Bin (Poltekkes Kemenkes Jakarta III, 2023)
In basic clinical laboratories, the availability of chemicals to create a test solution (reagent) is frequently limited or non-existent, delaying the sample inspection procedure. In medical laboratories, the inability to create a test solution with a certain chemical compound is a common constraint. The components of Turk's reagent are glacial acetic acid, gentian violet, and distilled water. The chemical glacial acetic acid, which is required to prepare Turk's reagent for leukocyte count testing, is frequently unavailable. To confirm that the counting of leukocytes may still be performed, it is required to find a readily available replacement to glacial acetic acid solution in turk solution that serves the same purpose. This study was done to investigate the viability of substituting extract Citrus limon for glacial acetic acid in the production of Turk's solution for the measurement of leukocyte counts. The study was developed as an experiment and conducted at Prof. Dr. Hamka's Medical Laboratory Technology Laboratory at Muhammadiyah University in Jakarta. In this investigation, a total of 30 blood samples containing the anticoagulant Ethylenediaminetetraacetic acid (EDTA) were utilized. The samples were separated into three treatment groups, each containing 10 samples: lemon treatments with concentrations of 2%, 3%, and 4%. Comparing the results of the study with those of controls using Turk solution revealed that lemon juice can be substituted for glacial acetic acid in Turk solution for determining the number of leukocytes, with a concentration of 2% being optimal.